Inkubasi Kewirausahaan Agribisnis Pada Kelembagaan Ekonomi Petani Organik Mukti Sadaya Menuju Usaha Bernilai Tambah - Herdiansyah Gustira Pramudia Suryono; Dematria Pringgabayu; Ashri Putri Rahadi; Yogi Suprayogi (Cahaya Pengabdian, 2026)
The Organic Farmers Economic Institution (KEP Organik Mukti Sadaya) encountered several challenges in developing its agribusiness, including dependence on selling unhusked rice and bulk rice, the absence of a structured business model, limited capability in calculating the Cost of Goods Sold (COGS), and inadequate product branding and marketing strategies. This community service program aimed to strengthen the entrepreneurial capacity of farmers through the implementation of an Agribusiness Entrepreneurship Incubation Model. The program was conducted over five months using participatory training, business coaching, implementation, and continuous monitoring and evaluation. The incubation process consisted of five stages: needs assessment, entrepreneurial mindset development, business development, implementation, and program evaluation. The results showed that the participants successfully developed a Business Model Canvas (BMC), calculated the Cost of Goods Sold (COGS), established product branding and packaging, designed digital marketing strategies, and prepared a business development roadmap. The program also achieved a Community Satisfaction Index of 92.6%, indicating a very high level of participant satisfaction. The Agribusiness Entrepreneurship Incubation Model proved effective in supporting the transformation of farmer groups toward value-added and sustainable agribusiness